2008
DOI: 10.1371/journal.pone.0003065
|View full text |Cite
|
Sign up to set email alerts
|

Breast Tumor Cells with PI3K Mutation or HER2 Amplification Are Selectively Addicted to Akt Signaling

Abstract: BackgroundDysregulated PI3K/Akt signaling occurs commonly in breast cancers and is due to HER2 amplification, PI3K mutation or PTEN inactivation. The objective of this study was to determine the role of Akt activation in breast cancer as a function of mechanism of activation and whether inhibition of Akt signaling is a feasible approach to therapy.Methodology/Principal FindingsA selective allosteric inhibitor of Akt kinase was used to interrogate a panel of breast cancer cell lines characterized for genetic le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
243
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(263 citation statements)
references
References 39 publications
18
243
0
2
Order By: Relevance
“…In accordance with our findings, She et al (2008) demonstrated that inhibition of AKT1/2 in HCC1806, a triple-negative cell line with wild-type PIK3CA, did not reduce P-S6RP (S235/236) despite the fact that P-AKT (S473) and p70S6K (T389) levels The YB-1/PIK3CA/uPA network promotes invasion A Astanehe et al were decreased. We suspect this is because RSK remains activated.…”
Section: Mda-mb-231supporting
confidence: 91%
See 1 more Smart Citation
“…In accordance with our findings, She et al (2008) demonstrated that inhibition of AKT1/2 in HCC1806, a triple-negative cell line with wild-type PIK3CA, did not reduce P-S6RP (S235/236) despite the fact that P-AKT (S473) and p70S6K (T389) levels The YB-1/PIK3CA/uPA network promotes invasion A Astanehe et al were decreased. We suspect this is because RSK remains activated.…”
Section: Mda-mb-231supporting
confidence: 91%
“…Interestingly, She et al (2008) used a potent inhibitor of AKT1 and AKT2 (AKTi-1/2) on various breast cancer cell lines and demonstrated that those with wild-type PIK3CA, including MDA-MB-231 that were used in our studies, were resistant to the effect of AKTi-1/2 even at concentrations leading to complete loss of P-AKT, whereas cells with PIK3CA mutations or HER2 amplifications were uniformly sensitive. They concluded that cells with PIK3CA mutations are dependent on AKT signaling whereas those with wild-type PIK3CA are not.…”
Section: Mda-mb-231mentioning
confidence: 85%
“…Treatment with MK-2206 first might lead to the accumulation of G 1 -phase cells limiting the activity of Mphase-specific chemotherapy. 14 Gastric cancer, similar to other malignancies, is a genetically heterogeneous disease: Inhibition of one pathway is never sufficient as other pathways often compensate. Our results show that common molecular findings in human malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Of these seven cell lines, the three with the highest levels of FABP5 mRNA (Hs578T, HTB-129, and MDA-MB231) have been reported to be negative for ER and PR. 26,27 MDA-MB231 is also negative for HER2, 27 but the HER2 status of HTB-129 and Hs578T is not known.…”
Section: Expression Of Fabp5 Mrna In Human Breast Cancer Tumors and Cmentioning
confidence: 99%